2011
DOI: 10.15282/ijame.4.2011.8.0038
|View full text |Cite
|
Sign up to set email alerts
|

Metal Matrix Composite Brake Rotor: Historical Development and Product Life Cycle Analysis

Abstract: Metal matrix composites (MMCs) have become attractive for engineering structural applications due to their excellent specific strength and are increasingly seen as an alternative to conventional materials, particularly in the automotive industry. In this study, a historical background on the development and application of metal matrix composites for automotive brake rotors is presented. The discussion also includes an analysis of the product life cycle with stir casting as a case study. The historical review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(74 citation statements)
references
References 11 publications
0
69
0
5
Order By: Relevance
“…In a recent study, a sandwich structure composite was developed using bamboo reinforced epoxy [28]. In addition, the feasibility of natural fiber composite material for engineering application has been studied extensively [29]. The main concept proposed in this work was using natural fiber composite laminates as the intermediate layer between aluminium skins and expanded polystyrene core to produce a hybrid composite sandwich panel.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, a sandwich structure composite was developed using bamboo reinforced epoxy [28]. In addition, the feasibility of natural fiber composite material for engineering application has been studied extensively [29]. The main concept proposed in this work was using natural fiber composite laminates as the intermediate layer between aluminium skins and expanded polystyrene core to produce a hybrid composite sandwich panel.…”
Section: Introductionmentioning
confidence: 99%
“…The SiCp was preheated to 900°C whereas the Al 6061 alloy was superheated to a temperature of 750°C. The previous study showed that 10% SiC is the best reinforcement for aluminium matrix composite [7]; however, in this study 1% Mg was added as a wetting agent, hence, SiC percentage was reduced to 9%. The aluminium matrix composite (AMC) was prepared into four different constituent sizes with 9 wt% silicon carbide particulate (SiCp) and 1% Mg formulations as indicated in Table 1.…”
Section: Methodsmentioning
confidence: 74%
“…From the image of the AMC IV sample (Figure 3), the worn surface was characterised by the localised shallow grooves and very fine scratches under SEM micrograph. This is due to the load bearing capacity of the particle mixture [7,19]. It is noteworthy that MPS along with Mg element in AMC showed better performance in terms of hardness and wear resistance.…”
Section: Wear Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…These MMCs have various properties depending on the shape, size, properties, volume fraction and distribution of the reinforcement material, properties of the matrix materials and compatibility of the matrix and reinforcement (Adebisi, Maleque, & Rahman, 2011;Ala-Kleme, Kivikytö-Reponen, Liimatainen, Hellman, & Hannula, 2006;Bhaskar & Sharief, 2012;Rahman, Kadirgama, et al, 2009). MMC generally consists of a light weight metal as the matrix element, and the fibers, whiskers or particles as the reinforcing element (Aeyzarq Muhammad Hadzreel & Siti Rabiatull Aisha, 2013;Conceição António & Paulo Davim, 2002).…”
Section: Introductionmentioning
confidence: 99%